A Study On Association of Thyroid Hormone and Intensive Care Unit Mortality in Central India. : Life Sciences- Medicine - Dandekar, DrPravin Gulab; Anil Jain, Dr Pranay; Jain, Dr Shefali (International Journal of Life Science and Pharma Research, 2023)
Thyroid dysfunction has been linked to mortality in patients hospitalized in the intensive care unit (ICU). We aim tostudy the thyroid hormone level changes in critically ill ICU patients and predict mortality based on thyroid hormone levels. Thisprospective observational study was conducted on 80 consecutive patients aged over 18yrs, from November 2021 to May 2022,in patients admitted to ICU at Chirayu medical college and Hospital, Bhopal, and followed up during their ICU stay. Samples weretested for T3, T4, and TSH on day 1 and day 7. In our study of 80 participants, 46(57.5%) were male, and 34(42.5%) were female.About 32 (40%) were non-survivors. The significance value (P value) of T3 levels on day 1 was 0.083, and on day 7 was 0.001; T4levels on day 1 were 0.85, and on day 7 was 0.001. Similarly, the significance of TSH levels on day 1 was 0.085, and on day 7 was0.001. Day 1 levels of T3 are significantly correlated with APACHE II Score, and Day 7 levels of T3, T4, and TSH significantlycorrelated with APACHE II scores in predicting the outcome of the patients with the higher significance of T3 compared to T4and TSH. Our study showed that low T3 level during critical illness increases mortality risk. Thyroid profiles can be used inpredicting mortality and as an independent factor in predicting the outcome of ICU patients.